SISTEM INFORMASI REKAM MEDIS BERBASIS WEB DI PRAKTEK DOKTER UMUM DR. SITI HODIJAH - Avifah Dian Permatasari; Amali; Ismasari Nawangsih (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
Currently practicing general practitioner dr. SITI HODIJAH still provides services to patients manually which are recorded in a book starting from patient registration, examination, treatment, action, recording of patient reports, billing of fees and results of patient reports which can cause errors, inaccurate reports and delays in information services when processed. Therefore we need a web-based medical record information system to display patient medical record data quickly and easily and provide convenience in manufacturing. This system is made web-based, using the PHP programming language and MySQL database. In planning the system using UML and the waterfall method is used as a system development method and uses the Laravel framework. The results of the research are in the form of a web-based patient medical record information system that can assist in managing patient data and reducing the risk of losing patient data as well as displaying medical record data quickly and easily. In placing the system, you can use hosting or localhost, which can be adjusted to your needs.